Forehearing words: Pre-activation of word endings at word onset. (29th September 2017) - Roll, Mikael; Söderström, Pelle; Frid, Johan; Mannfolk, Peter; Horne, Merle
Highlights: Neurophysiological pre-activation negativity (PrAN) found 136 ms after word onset. PrAN increased with decrease in number of possible word completions. PrAN increased with word frequency of possible word completions. Likely PrAN sources: pars opercularis of left IFG, angular gyrus of parietal lobe. Results suggest that PrAN reflects lexical selection. Abstract: Occurring at rates up to 6–7 syllables per second, speech perception and understanding involves rapid identification of speech sounds and pre-activation of morphemes and words. Using event-related potentials (ERPs) and functional magnetic resonance imaging (fMRI), we investigated the time-course and neural sources of pre-activation of word endings as participants heard the beginning of unfolding words. ERPs showed a pre-activation negativity (PrAN) for word beginnings (first two segmental phonemes) with few possible completions. PrAN increased gradually as the number of possible completions of word onsets decreased and the lexical frequency of the completions increased. The early brain potential effect for few possible word completions was associated with a blood-oxygen-level-dependent (BOLD) contrast increase in Broca's area (pars opercularis of the left inferior frontal gyrus) and angular gyrus of the left parietal lobe. We suggest early involvement of the left prefrontal cortex in inhibiting irrelevant left parietal activation during lexical selection. The results further our understanding of the importance of Broca's area in rapid online pre-activation of words.